POTENSI DAN TANTANGAN PENGEMBANGAN SUKUK WAKAF, KHUSUSNYA CASH WAQF LINKED SUKUK, SEBAGAI INSTRUMEN KEUANGAN SOSIAL ISLAM DI ERA MODERN - Nurfatra, Daniel; Rifki, Faiz; Anwar, Syah Jehan Khalifatul; Waluyo, Waluyo (JISEF : Journal Of International Sharia Economics And Financial, 2025)
This study analyzes the potential and challenges in developing Waqf Sukuk, particularly Cash Waqf Linked Sukuk (CWLS), as an Islamic social finance instrument in Indonesia. CWLS, which integrates cash waqf with state sukuk, offers great potential in a safe and impactful Islamic investment alternative, as well as expanding the investor base, and mobilizing funds for social projects and infrastructure projects that can empower communities, supported by existing regulations and examples of success in other countries as supporting facts. However, the challenges are quite severe, which include low Islamic financial literacy, religious dimensions that need to be strengthened, and limited development of supporting ecosystems. This research uses a descriptive qualitative approach and literature study to provide comprehensive policy recommendations to encourage community participation in CWLS to realize its strategic role in sustainable development in Indonesia and to become a global model in the development of Islamic social finance. Translated with DeepL.com (free version)